Aphidophagous ladybird beetles adapt to an aphid symbiont. (30th July 2022) - Du, Xue‐Yong; Yang, Huan‐Ying; Gong, Sen‐Rui; Zhang, Pei‐Fang; Chen, Pei‐Tao; Liang, Yuan‐Sen; Huang, Yu‐Hao; Tang, Xue‐Fei; Chen, Qiao‐Kui; De Clercq, Patrick; Li, Hao‐Sen; Pang, Hong
Abstract: Bacterial symbionts can play a key role in the interactions between trophic levels. Certain symbionts are known to confer protection against natural enemies of their arthropod hosts. However, whether natural enemies evolve and adapt to prey symbionts is not well understood. In this study, we found that a free‐living strain of aphid symbiont Serratia symbiotica, SsMj, was the most discriminative biomarker of the aphid feeding in the microbiota of aphidophagous (aphid‐feeding) ladybirds. Moreover, SsMj persisted in the digestive tract of starved ladybirds and did not decay together with ingested aphid materials, suggesting horizontal transmission across trophic levels. We further found that SsMj did not necessarily exhibit a negative impact on aphidophagous ladybirds of the Coccinellini tribe in contrast with other, non‐aphidophagous, ladybirds. First, starvation did not significantly change SsMj relative abundance or alpha microbiota diversity of an aphidophagous ladybird. Second, diets containing SsMj did not decrease the performance of the aphidophagous ladybirds. Third, infection with SsMj through injection had a minor impact on the survival of aphidophagous ladybirds. Together, our evidence suggests that the aphid symbiont S. symbiotica can be horizontally transmitted to ladybird predators. At the same time, the group of ladybirds that have adapted to feeding on aphids have also evolved to establish a nearly neutral relationship with S. symbiotica, suggesting adaptation to a prey symbiont. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog. Abstract: 细菌共生菌可以在不同营养级间生物的相互作用中起关键作用。其中一些共生菌可以帮助它们的节肢动物宿主抵御天敌。但是，我们仍不清楚天敌是否进化去适应它们猎物的共生菌。 本研究，我们发现一株营自由生活的蚜虫共生菌 Serratia symbiotica (命名为SsMj)，是瓢虫取食蚜虫后瓢虫微生物组中相对丰度上升程度最大的细菌。不仅如此，SsMj不会随蚜虫一起被瓢虫消化掉，而是留存在瓢虫的消化道，说明它发生跨营养级的传播。 我们进一步发现SsMj不一定对蚜食性的瓢虫有负面的影响。首先，饥饿不会显著影响蚜食性瓢虫体内的SsMj相对丰度和微生物组的alpha多样性。然后，蚜食性的瓢虫不会因为取食添加SsMj的食物而表现力下降。最后，通过注射感染SsMj较轻微地降低蚜食性瓢虫的存活率。相对而言，SsMj对其它瓢虫有显著的负面影响。 总的来说，我们的证据表明一种蚜虫的共生菌 S. symbiotica 可以水平传播至蚜虫的捕食者瓢虫。另一方面，瓢虫中一个偏好食蚜的支系则通过适应进化，与 S. symbiotica 建立了一种近乎中性的关系。